2009
DOI: 10.1155/2009/578610
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hyperprolactinemia and Bilateral Galactocele in a Male Infant

Abstract: Galactocele is a benign breast lesion, usually occurring in nursing women. This lesion is a rare cause of breast enlargement in children. In this paper we describe the case of an infant with hyperprolactinemia (which persisted throughout 15 years of clinical observation) and bilateral galactocele. We speculate that a congenital midline defect in our patient might have impaired the normal dopaminergic inhibitory tone on pituitary lactotroph cells, thus leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…22 The first case of a galactocele was reported back in 1880 10 and since then only another 23 cases have been published, usually as a single case reports, with only 2 articles describing 3 and 2 cases, respectively 13,20 (►Table 1). Galactoceles are frequently unilateral but in over 30% of cases (8/26) they occurred bilaterally 3,8,12,15,16,20,21 (►Table 1). The median age at onset was 7 months, and the median age at clinical presentation was 15 months (►Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…22 The first case of a galactocele was reported back in 1880 10 and since then only another 23 cases have been published, usually as a single case reports, with only 2 articles describing 3 and 2 cases, respectively 13,20 (►Table 1). Galactoceles are frequently unilateral but in over 30% of cases (8/26) they occurred bilaterally 3,8,12,15,16,20,21 (►Table 1). The median age at onset was 7 months, and the median age at clinical presentation was 15 months (►Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…20,23 Galactocele can occur in cases with persistent hyperprolactinemia. 21 Furthermore, elevated insulin-like growth factor-I resulting from growth hormone treatment of congenital hypopituitarism has been reported to contribute to the enlargement of galactocele. 19 No endocrine abnormalities were found in one of our patient whereas the other one had no further tests done as they were regarded as unnecessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lau et al found scanty lymphocytes and absence of malignant cell in aspirated fluid from galactocele of 16‐month‐old boy . Tomasi et al described presence of very rare histiocytes and lymphocytes at the cytological analysis of the aspirated milky fluid from galactocele of 26‐month‐old boy . Histopathological examination of the resected specimens showed cysts containing milk like fluid, lined by cuboidal to columnar epithelium where some of the epithelial cells had clear intracytoplasmic secretory vacuoles …”
Section: Discussionmentioning
confidence: 99%